Tracing Historical Linguistic Kinship: A Lexicostatistical Study on Dayak Ngaju and Banjar Kuala Languages in Kalimantan - Tiara Dwi Saputri Saputri; Misrita; Imam Qalyubi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study investigates the lexical kinship between the Dayak Ngaju and Banjar Kuala languages in Kalimantan through a lexicostatistical approach, driven by the urgent need to map and preserve under-researched Austronesian languages. The primary aim is to determine the degree of linguistic relatedness based on core vocabulary and to classify their historical relationship. Employing a quantitative descriptive design, the study analyzed 200 basic vocabulary items drawn from Lexirumah and the Austronesian Basic Vocabulary Database using purposive sampling. Data were processed using Microsoft Excel and analyzed through Swadesh’s lexicostatistical formula to calculate the percentage of cognates and determine the genealogical classification. The results reveal a lexical similarity of 31%, categorizing the relationship as a “stock” level of kinship according to Keraf’s classification. These findings support the hypothesis that the two languages share a historical connection, confirming systematic phonological correspondences such as apocope, apheresis, and metathesis. The study contributes to comparative historical linguistics and provides practical implications for language preservation, curriculum development, and further field-based linguistic research in Kalimantan and beyond.